Internal and External Parasitic Infections of Equines In South Darfur State, Western Sudan (Journal of Veterinary Medicine and Animal Production, 2021)
In a retrospective study of 20 years, 6675 horses and donkeys were examined for different diseases and this study was focused on internal and external parasitic infections. Of the 6675 equines examined, 3275 (49.1%) were infected with different diseases and the rest were physical, nutritional or undiagnosed cases. The parasites infected 2887 (88.2%) of the 3275 diseased animals and 43.3% of the equines examined. The infections were solely or associated with other diseases. The parasites found in the equines were: strongyles (37.8%), strongyloides sp. (1.7%), Oxyuris equi(1.6%), Parascaris equarum(1.59%), mange mites(0.4%), Anopolocephala sp. (0.75%) and Coccidia like species (0.06%). Fungal infections which infected 39(0.58%)of the equines were diagnosed concomitantly with the external parasites. The common ticks collected from the horses and donkeys were Hyalomma spp. Amblyomma lepidum, Boophilus and Rhipicephalus spp. The common flies associated with the equines, were from the genera Musca, Tabanus, Stomoxys, Gasrtophilus, Haematobia, Anopheles, Culex, Culicoides, Aedes, Hippobosca, Lucelia, Phlebotomus and in southern areas of South Darfur, Glossina and Simulium. Monthly mean incidents showed that the infections occurred throughout the year, but their peak levels were in summer (March to June) and late rainy seasons (September to November) for reasons discussed. Medicines which were used for treatment of the infected equines were reviewed and protocols for treatment and control of parasites in equines were suggested. Infections with blood parasites will be dealt with in a separate paper.